KECERDASAN SPIRITUAL AUDITOR MENGGUNAKAN ANALISIS MODEL RASCH - Dewi Anggraeni; Yoga Adhy Nugraha (Universitas Islam Negeri Alauddin Makassar, 2019)
ABSTRAKKecerdasan spiritual merupakan salah satu faktor yang dapat membantu auditor melakukan penyalahgunaan laporan keuangan. Kajian ini bertujuan untuk menganalisis kecerdasan auditor menggunakan analisis model Rasch. Responden yang berpartisipasi dalam kajian ini berjumlah 105 auditor yang bekerja di Perusahaan. Kecerdasan spiritual diukur menggunakan angket, kemudian dianalisis menggunakan Rasch Model. Hasil kajian menunjukkan 49,52 % auditor mempunyai kecenderungan kecerdasan spiritual tinggi, sebanyak 50,42% auditor mempunyai kecenderungan kecerdasan spiritual sedang dan 1,90% auditor mempunyai kecenderungan kecerdasan spiritual rendah.Keyword: Kecerdasan Spiritual, Auditor, Model Rasch ABSTRACT Spiritual intelligence is one of the factors that can help auditors misuse financial statements. This study aims to analyze auditor intelligence using the Rasch model analysis. Respondents who participated in this study totaled 105 auditors working in the Company. Spiritual intelligence is measured using a questionnaire, and then analyzed using the Rasch Model. The results of the study showed 49.52% of auditors had a tendency for high spiritual intelligence, 50.42% of auditors had a tendency for moderate spiritual intelligence and 1.90% of auditors had a tendency for low spiritual intelligence.Keyword: Spiritual Intelligence, Auditor, Rasch Model